PENGARUH KOMPRES HANGAT TERHADAP NYERI DISMENORE PADA REMAJA: LITERATURE REVIEW - Astrit Novitaningsih; Maharani Lentera Putri; Uswatun Khasanah; Tri Sunarsih; Dechoni Rahmawati (Jurnal Ilmiah Kebidanan Imelda, 2024)
Dysmenorrhea is pain in the lower abdomen before and during menstruation. Dysmenorrhea is not dangerous, but can interfere with physical activities and if left untreated can be annoying and cause discomfort. According to WHO (World Health Organization), dysmenorrhea was found in 1,769,425 (90%) women, of which 10-15% suffered from severe dysmenorrhea. Dysmenorrhea pain can be treated non-pharmacologically, one way is by using warm compresses. The aim of this literature review is to determine the effect of giving warm compresses to adolescents on the intensity of dysmenorrhea pain. The design used is a literature review. Literature search through several international and national literature search databases including Google Scholar, Mendeley, and Garuda. The study sources used from 2017-2022 used PRISMA. After selecting 6 journals that met the criteria and showed how applying warm compresses helped dysmenorrhea patients feel better, a review was carried out. Based on the articles collected, the results showed that warm compresses can reduce dysmenorrhea pain.